A Review of Official Documents and Literature on the Forgotten Victims of Parental Incarceration in South Africa - Magadla-Mateyise, Afika Fikiswa; Zenzile, Enoch (Research in Social Sciences and Technology, 2024)
This article is a literature synthesis of the living conditions of black children after their parent's imprisonment. In Africa, the prison population currently stands at 1,194,497, while in South Africa, 147,922 people were being held in correctional facilities as of January 2021. Parental incarceration has affected all children, regardless of race, age, or cultural background. An increasing amount of research indicates that children with incarcerated parents are prone to internalized behaviors such as depression, anxiety, and withdrawal, as well as externalized behaviors including criminality and substance use. They may also experience cognitive delays, academic struggles, and insecure attachments in their relationships with both their imprisoned parents and primary caregivers. The term "caregiver" denotes the individual who assumes the role of the child's main caregiver while the parents are incarcerated. It is important to note that the literature focusing on child-headed households in South African informal settlements and townships may be limited. This paper is a narrative synthesis of the literature review and uses secondary sources.